내면화와 외현화 행동문제집단과 정상집단 아동의 인구학적, 가족기능적 특성의 차이 - 정문자(Moon Ja Chung); 이미리(Mee Ry Lee); 전연진(Yeon Jin Jeon) (Korean Journal of child studies, 2007)
Participants in this study were 1.245 4th and 5th graders and their parents from 8 elementary schools in Seoul, Daejeon, and Pusan. Using the Korean Youth Self-Report (K-YSR), children's behavior problems were measured and assigned to either clinical or normal groups. Between group differences were that the educational level of mothers of internalizing girls was lower than that of normal girls. Girls with internalizing problems had more siblings than normal girls. Parents of both boys and girls with either internalizing or externalizing problems were more rejecting and/or permissive than parents of children without behavior problems. Fathers of children with behavior problems perceived more marital conflicts, while mothers whose children have behavior problems had more negative family-of-origin experiences compared to parents of normal children.